Psychosocial care network: managers' perception and tensions of the field - Rosimár Alves Querino; Rafael Silvério Borges; Letícia Yamawaka de Almeida; Jaqueline Lemos de Oliveira; Jacqueline de Souza
ABSTRACT Objective: to analyze the perception of workers and managers about the psychosocial care network in a medium-sized municipality in the inlands of the state of Minas Gerais. Method: qualitative, descriptive and exploratory study involving twelve participants from different points of the network. The semi-structured interviews were analyzed in the light of Pierre Bourdieu's framework of constructionist structuralism. Results: the actions offered by the services were based on the perspectives of resocialization, user embracement, group and multiprofessional care, and on approaches to harm reduction, recreation and daily organization. These were configured as the network resources/capital. Tensions were identified in family embracement and in relationships between families and users, as well as in the prejudice towards people with mental disorders. Final considerations: the social agents were willing to contribute to processes of change in order to overcome the focus on specialties, the lack of training of some teams, lack of infrastructure and of some components, especially those related to leisure and community life.